Preliminary study of endoparasite fauna of hirundo sp: a case study at Universiti Teknologi Mara Negeri Sembilan / Hasnorsharmini Hassan - Hassan, Hasnorsharmini (2014)
Parasites are organisms that live in or on another organism and gain an advantage at the expense of the host. A study was carried out in UiTM Negeri Sembilan to identify the presence of endoparasites infesting the Barn Swallow {Hirundo rustica) and the Pacific Swallow {Hirundo tahitica). The prevalence of endoparasites in blood and droppings of the birds were also conducted. Fecal and blood samples were collected from a total number of 86 birds, Hirundo sp comprising of 46 Hirundo tahitica and 40 Hirundo rustica. All samples were individually collected. The fecal samples were examined using the fecal flotation technique and blood sample was examined by blood smear. The prevalence of endoparasites was found to be higher infested on Hirundo tahitica (56.36%) compared to Hirundo rustica (43.64%). Coccidia was found the most frequently prevalent (55.45%) to both species compared to strongyle (44.55%). At 5% significance level, it was concluded that there is no relationship between the type of birds which are the Pacific Swallow {Hirundo tahitica) and the Barn Swallow {Hirundo rustica) with the endoparasites (strongyle and coccidia). As the results may have been influenced by the exposure to contaminated food and the surrounding agricultural environment. This study also shown that parasite was not found detected in the blood due to the absence or scarcity of proper vectors and the host immunological capabilities to prevent infection of parasites.